403 Inferior Clinical Outcomes for Patients with Medicaid Insurance Following Surgery for Degenerative Lumbar Spondylolisthesis: A Prospective Registry Analysis of 608 Patients. (April 2023) - Chan, Andrew K.; Letchuman, Vijay; Mummaneni, Praveen V.; Burke, John Frederick; Agarwal, Nitin; Randy Bisson, Erica Fay; Bydon, Mohamad; Foley, Kevin T.; Shaffrey, Christopher I.; Glassman, Steven D.; Wang, Michael Y.; Park, Paul; et al.
Abstract : INTRODUCTION: It remains unclear how type of insurance coverage impacts long-term, spine-specific patient-reported outcomes (PROs). METHODS: The prospective Quality Outcomes Database registry was queried for patients with grade 1 degenerative lumbar spondylolisthesis who underwent single-segment surgery. 24-month PROs compared included Oswestry Disability Index (ODI), Numeric Rating Scale Back Pain (NRS-BP), NRS Leg Pain (NRS-LP), EuroQol-5D (EQ-5D), and North American Spine Society (NASS) Satisfaction. RESULTS: 608 patients undergoing surgery for grade 1 degenerative lumbar spondylolisthesis (mean age 62.5 ± 11.5 years and 59.2% women) were selected. Insurance types included private insurance (n = 319, 52.5%), Medicare (n = 235, 38.7%), Medicaid (n = 36, 5.9%), and VA/government (n =17, 2.8%). 1 patient (0.2%) was uninsured and was removed from the analyses. In adjusted multivariable analyses, when compared to patients with private insurance, Medicaid was associated with worse 24-month postoperative ODI β = 10.2, 95% CI 3.9 - 16.5) and NRS-LP β = 1.3, 95% CI 0.3 - 2.4). Medicaid was associated with worse EQ-5D scores compared to private insurance (β = -0.07, 95% CI -0.01 - -0.14), but not when compared to Medicare and VA/government insurance (p > 0.05). Medicaid was associated with lower odds of reaching ODI minimal clinically important difference (OR = 0.2, 95% CI 0.03 - 0.7) compared to VA/government insurance. NRS-BP and NASS satisfaction did not differ by insurance coverage (p > 0.05). CONCLUSIONS: Despite adjusting for potential confounding variables, Medicaid coverage was independently associated with worse 24-month PROs following lumbar spondylolisthesis surgery compared to other payer types. While all improved postoperatively, those with Medicaid coverage had relatively inferior improvements.